2020
DOI: 10.1111/1748-8583.12271
|View full text |Cite
|
Sign up to set email alerts
|

Alternative balanced scorecards built from paradigm models in strategic HRM and employment/industrial relations and used to measure the state of employment relations and HR system performance across U.S. workplaces

Abstract: This paper constructs alternative balanced scorecards based on high‐performance work system (HPWS) and employment relations system (ERS) models. The models are depicted and compared in diagrams and used as framework skeletons for building separate HPWS and ERS scorecards, intended to provide a detailed data picture of the operational health and performance of an organization's employment/HR system and its operations, processes, and inputs/outputs. The scorecards are filled in with nationally representative dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…Does a necessary focus on 'business acumen' and topics such as strategic HRM and performance drive out or come at the expense of more pluralistic models of HR that emphasise the importance of how HR impacts on stakeholders? This is important because different paradigm models of HRM lead to quite different conclusions about the state of HRM and its consequences (Kaufman et al, 2021). It is therefore important for professional bodies to promote models that recognise the importance and legitimacy of stakeholder interests.…”
Section: What Next For Hr?mentioning
confidence: 99%
“…Does a necessary focus on 'business acumen' and topics such as strategic HRM and performance drive out or come at the expense of more pluralistic models of HR that emphasise the importance of how HR impacts on stakeholders? This is important because different paradigm models of HRM lead to quite different conclusions about the state of HRM and its consequences (Kaufman et al, 2021). It is therefore important for professional bodies to promote models that recognise the importance and legitimacy of stakeholder interests.…”
Section: What Next For Hr?mentioning
confidence: 99%
“…Moreover, the results of this study show that the process of defining and using HR metrics is not simple; it can give rise to disagreements that concern the definition of metrics and their use. The literature has already addressed the question of appropriate and inappropriate metrics (Chhinzer and Ghatehorde, 2009; Kaufman et al , 2021; Tootell et al , 2009), but has not given specific examples of conflicts or disagreements and therefore has not studied the conflict resolution process. Tootell et al (2009) mention that “inappropriate measures simply encourage inappropriate behaviours not in the long-term interests of the business” (p. 375) and offer edifying conclusions regarding how difficult it is for the HR function to know how to measure things properly and to gain acceptance of the measures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these publications first underlined the ability of HR metrics to improve the contribution of the HR function to organizational performance (Welbourne, 2006; Wolfe et al , 2006) and demonstrated this ability (Doherty and Norton, 2014; Murphy and Zandvakili, 2000). Second, they contributed to the definition of a set of metrics useful for managing human resources (Fitz-enz and Davison, 2002; Kaufman et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary research on the pluralist frame has focused principally on examining how it has adapted (or indeed failed to adapt) to the significant changes affecting work; namely, the breakdown of the traditional breadwinner model of male, full-time employment occurring in large manufacturing workplaces governed as they were by a prevailing structure of unionised collective bargaining. Ackers (2002) argues that pluralism has failed to move beyond its core assumption of the primacy of unions and collective bargaining that reflected the system of the 1970s much more than contemporary employment relations, whereas, at least through the efforts of authors such as Kelly (1988), Marxist analysis has engaged in some critical self-reflection and revision to reflect modern workplace realities.…”
mentioning
confidence: 99%